Efeito da irrigação no rendimento e na qualidade dos tubérculos na cultura da batata (Solanum tuberosum L.) - Franke, Alberto E.; Martini, Luis C. P.; Konig, Osvaldo; Pozzebon, Éder; Liberalesso, R. A. (Revista Ceres, 2015)
.